DETERMINING VALUE AT RISK USING EXTREME VALUE THEORY ON A FINANCIAL DATA SET - Gjorgiev, Stevo; Gacovska-Barandovska, Aneta (Matematichki Bilten, 2024)
Extreme value theory has a wide range of applications. The paper considers application of extreme value theory in the area of financial flows. Our data set has been processed using two different methods, block maxima and peak over the threshold method. We compare the obtained results for the risk measures and draw conclusions on the behavior of the financial flows for different time intervals.